The Use of Intrinsic Disorder and Phosphorylation by Oncogenic Viral Proteins to Dysregulate the Host Cell Cycle Through Interaction with pRb - Heidi Kast-Woelbern; Sarah K. Martinho; Kayla T. Julio; Audrey M. Vazzana; Abbey E. Mandagie; Ariane L. Jansma (Viruses)
Approximately 15% of cancers worldwide are caused by oncogenic viruses. These infectious agents utilize multiple strategies to dysregulate their host cells as a means of viral reproduction. While this typically involves a small number of viral oncoproteins known to interact with a myriad of host cell proteins, direct binding with the tumor suppressor retinoblastoma protein (pRb) as a means to dysregulate the cell cycle appears to be a common mechanism among most known oncogenic viruses. This review evaluates the shared structural themes of binding motif, intrinsic disorder, and viral oncoprotein phosphorylation, utilized by eight different oncogenic viruses for the subjugation of pRb. Cancer caused by oncogenic viruses represents one of the few potentially preventable forms of cancer. The more we understand the common strategies used by these infectious agents, the better equipped we will be to further optimize vaccination and therapeutic strategies to fight them.